Effectiveness of m-health based self-management on self-efficacy in patients with cancer: A systematic review and meta-analysis - Anakotta, Olivya; Rochmawati, Erna; Saidi, Sanisah Binti (Jurnal Ners, 2023)
Introduction: M-health has been developed and tested through studies in various settings and found was useful for providing knowledge and experience for nurses in cancer care settings. However, none has synthesized the effectiveness of m-health on self-management of patients with cancer. To evaluate the effect of interventions using mobile-based application on patient's self-management. Outcome measures were patients' medical adherence, self-efficacy and self-management level and health literacy. Method: The review is reported in accordance with the guidelines of the PRISMA statement. A systematic was conducted in five databases. Randomized controlled trials and quasi-experimental trial were eligible for inclusion.   Results: Eight studies were included. There was a significant effect on self-efficacy after interventions using mobile-based applications (SMD = 0.36, CI 95%, [0.16, 0.56], p < 0.00006). Qualitative synthesis shows that the use of m-health can improve changes in health behavior, health literacy and physical activity. Conclusion: M-health app interventions may improve self-efficacy in cancer patients. Meanwhile, changes in health behavior in patients can be significantly improved using m-health based self-management. M-health can be integrated into health services for the management of patients with cancer.